1971
DOI: 10.1017/s002193200000821x
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness in Immigrant Minorities in London

Abstract: An epidemiological study has been made of rates of mental illness in a number of ethnic minorities who are immigrants to Britain, and have settled in a denned area of South London. Of the groups considered, those from Africa, the Old Commonwealth, India and Pakistan have the highest rates. The lowest rates were found in those from Cyprus and Malta, native Britons, and those from the Caribbean. After controlling for the effects of age, sex and social class it was found that the pattern of illness in a number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…The British data on Afro-Caribbeans is less clear cut. Community studies have produced conflicting results and no clear picture of the prevalence of minor psychiatric disorders across ethnic groups have emerged (Bagley, 1971;Cochrane & Stopes-Roe, 1981; Bebbington et al 1981). On balance, these studies do not provide adequate evidence to explain observed ethnic differences in consultation rates.…”
Section: Introductionmentioning
confidence: 99%
“…The British data on Afro-Caribbeans is less clear cut. Community studies have produced conflicting results and no clear picture of the prevalence of minor psychiatric disorders across ethnic groups have emerged (Bagley, 1971;Cochrane & Stopes-Roe, 1981; Bebbington et al 1981). On balance, these studies do not provide adequate evidence to explain observed ethnic differences in consultation rates.…”
Section: Introductionmentioning
confidence: 99%
“…The causative role of racism in the aetiology of the high rates of schizophrenia in England has also been suggested by Bagley (1971Bagley ( , 1975, Littlewood & Lipsedge (1981), and Burke (1984). Bagley (1971) concluded that social stress factors can influence the onset of schizophrenia in Afro-Caribbeans and that "status striving in a climate of limited opportunity" is significantly associated with schizophrenia in West Indians. Ineichen (1991) concludes that oppression, whether through racism or family dynamics may produce behaviour which leads to an eventual diagnosis of schizophrenia.…”
Section: Psychopathology In Jamaicamentioning
confidence: 88%
“…For a review of this literature (which implies that Bangladeshi women in Britain have higher rates of mental illness and suicidal behaviours than Bangladeshi males, several years after leaving Bangladesh) see Bagley [43]. These studies are not included in the present review.…”
Section: Methods Of Reviewmentioning
confidence: 99%